Resistance through Entrepreneurship: A Rereading of Nathaniel Hawthorne’s The Scarlet Letter (Sudurpaschim Spectrum, 2024)
In the Puritan setting of early America an act of adultery, one of the seven deadly sins, takes place with much shocking to the society and the religious authority. Between a married woman named Hester Prynne and a religious figure with influential personality called Arthur Dimmesdale there develops an illicit relation in the outskirts of the society. As an outcome of the sin Hester becomes pregnant and gives birth to a daughter which proves that in the extreme rigidity of the practice of Puritanism such an act of sin can take place which questions the validity of the religion. In the process of the trial scene, she vows not to reveal the name of her secret partner and decides to shoulder the punishment alone in a dramatic process of interrogation by the same man. Finally, Hester is given a compromised’ punishment to carry an alphabet 'A' around her neck meaning adulteress. Just after the moment Hester's new struggle of life for survival has started defying the religion, the society and the male authority. As a single mother of a daughter, she practices her skill of embroidery that results into an eventual attempt of entrepreneurship. With a bespoken performance through the needlework skill Hester’s actions are louder than her voice as women in the Puritan society are always voiceless with a binary (man/woman) interpretation where the second (woman) is deemed as inferior while the first (man) is superior. Drawing on the theories of entrepreneurship, identity, and the third space, this paper analyzes how Hester has resisted her position as a woman, a mother figure and abeloved and negotiated her evolving identities through the successful attempt of entrepreneurship, the impact of the Puritan punishment, and the ultimate transformation that shapes her new sense of the self.